Cuatro hermanas - Carleton, Jetta; Gispert, María Teresa; Carleton, Jetta (Barcelona, España : Libros del Asteroide S.L.U., 2012)
On a farm in western Missouri during the first half of the twentieth century, Matthew and Callie Soames create a life for themselves and raise four headstrong daughters. Jessica will break their hearts. Leonie will fall in love with the wrong man. Mary Jo will escape to New York. And wild child Mathy's fate will be the family's greatest tragedy. Over the decades they will love, deceive, comfort, forgive-- and, ultimately, they will come to cherish all the more fiercely the bonds of love that hold the family together.
Online resource; title from ePub title page (Digitalia, viewed March 14, 2018)
Keywords: Farm life -- Fiction; Missouri -- Fiction; Domestic fiction; Electronic books